Direct oral anticoagulant versus low-molecular-weight heparin for treatment of venous thromboembolism in cancer patients: An updated meta-analysis of randomized controlled trials. Issue 194 (October 2020) - Haykal, Tarek; Zayed, Yazan; Deliwala, Smit; Kerbage, Josiane; Ponnapalli, Anoosha; Malladi, Srikanth; Goranta, Sowmya; Samji, Varun; Adam, Soheir
Abstract: Background: Cancer associated venous thromboembolism (VTE) results in significant morbidity and mortality. Low molecular weight heparin (LMWH) has been standard of care for treatment of cancer-associated VTE, however direct oral anticoagulants (DOACs) are emerging as alternative treatment options. Objective: To compare the benefits and harms of DOACs versus LMWH for treatment of VTE in cancer. Data sources: MEDLINE, Embase, and the Cochrane Collaboration Central Register of Controlled Trials from inception to April 2020. Study selection: Randomized controlled trials (RCT) comparing DOACs with LMWH for treatment of VTE in cancer patients. Data synthesis: Four good-quality RCTs, met inclusion criteria. Compared with LMWH, DOACs were associated with lower rates of VTE recurrence (RR 0.62; 95% CI: 0.44–0.87; P = 0.006), and DVT recurrence (RR 0.61; 95% CI: 0.4–0.94; P = 0.02) but not PE recurrence (RR 0.73; 95% CI: 0.51–1.04; P = 0.08), in cancer patients. However, the risk of clinically relevant non-major bleeding (CRNMB) (RR 1.58; 95% CI: 1.11–2.24; P = 0.01), and major bleeding in gastrointestinal cancer (RR 2.55; 95% CI 1.24–5.27, P = 0.01), were higher with DOACs. The risk of overall major bleeding (RR 1.33; 95% CI: 0.84–2.1; P = 0.22), all-cause mortality (RR 0.99; 95% CI: 0.84–1.17; P = 0.92), VTE-related mortality (RR: 1; 95% CI: 0.29–3.44; P = 1) and bleeding-related mortality (RR: 0.71; 95% CI: 0.17–2.91; P = 0.63), were similar in both treatment groups. Conclusion: Among cancer patients with VTE, treatment with DOACs is associated with a significant reduction of VTE and DVT recurrence, compared to LMWH. These benefits were offset by an increased risk of CRNMB, and major bleeding in gastrointestinal cancer. Highlights: Among cancer patients with VTE, DOACs are associated with a significant reduction of VTE and DVT recurrence, compared to LMWH. The risk of major bleeding is similar in both treatment groups. In gastrointestinal cancer, the risk of major bleeding is significantly higher with DOACs.